Combined Effect of Kimchi Powder and Onion Peel Extract on Quality Characteristics of Emulsion Sausages Prepared with Irradiated Pork - Lee, Soo-Yoen (Korean J Food Sci Anim Resour, 2015)
This study was conducted to investigate the effects of kimchi powder and onion peel extract on the quality characteristics of emulsion sausage manufactured with irradiated pork. The emulsion sausages were formulated with 2% kimchi powder and/or 0.05% onion peel extract. The changes in pH value of all treatments were similar, depending on storage periods. The addition of kimchi powder increased the redness and yellowness of the emulsion sausage. The addition of onion peel extract decreased the thiobarbituric acid reactive substances value of the emulsion sausages prepared with irradiated pork. The volatile basic nitrogen value of the emulsion sausage prepared with kimchi powder was the highest, whereas that of the emulsion sausage prepared with onion peel extract was the lowest. The treatment without kimchi powder or onion peel extract and the treatments prepared with onion peel extract showed lower microbial populations than the other treatment. Sensory evaluations indicated that a higher acceptability was attained when kimchi powder was added to the emulsion sausages manufactured with irradiated pork. In conclusion, our results suggest that combined use of kimchi powder and onion peel extract could improve quality characteristics and shelf stability of the emulsion sausage formulated with irradiated pork during chilled storage.